Grazing high and low: Can we detect horse altitudinal mobility using high‐resolution isotope (δ13C and δ15N values) time series in tail hair? A case study in the Mongolian Altai. (29th August 2019) - Lazzerini, Nicolas; Coulon, Aurélie; Simon, Laurent; Marchina, Charlotte; Noost, Bayarkhuu; Lepetz, Sébastien; Zazzo, Antoine
Abstract : Rationale: Carbon and nitrogen stable isotope time series performed in continuously growing tissues (hair, tooth enamel) are commonly used to reconstruct the dietary history of modern and ancient animals. Predicting the effects of altitudinal mobility on animal δ 13 C and δ 15 N values remains difficult as several variables such as temperature, water availability or soil type can contribute to the isotope composition. Modern references adapted to the region of interest are therefore essential. Methods: Between June 2015 and July 2018, six free‐ranging domestic horses living in the Mongolian Altaï were fitted with GPS collars. Tail hairs were sampled each year, prepared for sequential C and N isotope analysis using EA‐IRMS. Isotopic variations were compared with altitudinal mobility, and Generalized Additive Mixed (GAMMs) models were used to model the effect of geographic and environmental factors on δ 13 C and δ 15 N values. Results: Less than half of the pasture changes were linked with a significant isotopic shift while numerous isotopic shifts did not correspond to any altitudinal mobility. Similar patterns of δ 13 C and δ 15 N variations were observed between the different horses, despite differences in mobility patterns. We propose that water availability as well as seasonal availability of N2 fixing type plants primarily controlled horse hair δ 13 C and δ 15 N values, overprinting the influence of altitude. Conclusions: Our study shows that altitudinal mobility is not the main factor that drives the variations in horse tail hair δ 13 C and δ 15 N values and that seasonal change in the animal dietary preference also plays an important role. It is therefore risky to interpret variations in δ 13 C and δ 15 N values of animal tissues in terms of altitudinal mobility alone, at least in C3 –dominated environments.